Different Health Scenarios to Prepare Calves for Shipping and for Receiving Yearling Cattle: VM113/VM081, 2/2002 - Richey, Eddie J. (EDIS, 2003)
This document is VM113, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 26, 2002. https://edis.ifas.ufl.edu/vm081